Russian experience in pediatric hematology-oncology: Collaboration of the national society and national centers - Kirill I. Kirgizov; Svetlana A. Kogan; Yana A. Erdomaeva; Garik B. Sagoyan; Guzel M. Muftakhova; Tatyana G. Shlyakhtina; Dina V. Birlyukova; Galina I. Serik; Galina A. Novichkova; Svetlana R. Varfolomeeva; Alexander G. Rumyantsev (Elsevier, 2020)
A vertically integrated management system in the health care sector in the Russian Federation is based on the model of functioning of national centers. One of the key components in achieving success is the interaction of national center with a leading national professional society. The aim of the article is to present the experience of joint work of the National Society of Pediatric Hematologists and Oncologists (NSPHO) with the leading centers of excellence in pediatric cancer care in Russia in the field of development of pediatric oncology-hematology in Russia. In order to accomplish the task of building a system of pediatric oncology-hematology care, a comprehensive development program was implemented, which included collecting data on the structure of the regional services and improvement of these services. Experience of creating of professional standards and the concept of a unified approach of training in pediatric oncology and hematology using the technology of continuing medical education are reflected. Other projects of NSPHO are represented too.